Kenaikan Berat Badan BBLR Selama Dirawat Di Rumah Sakit - Erna Rahma Yani; Triatmi Andri Yanuarini; Putri Rizki Amalia (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2019)
Weight gain is an important indicator in the care of Low Birth Weight Babies (LBW), but weight gain has many inhibiting factors, including babies experiencing hypoglycemia and hypothermia. LBW needs to be given intensive care in an incubator and kangaroo method care (KMC). The purpose of this study was to analyze the differences in weight gain of LBW treated in the incubator and KMC with LBW treated in the incubator. This study used a case-control design. The population of Gambiran Hospital is 55 babies, while the population of Aura Syifa Hospital is 155 babies. A sample of 98 LBW based on a simple random sampling technique. The research sample in Gambiran Hospital received incubator and KMC treatment, while the research sample at Aura Syifa Hospital received incubator treatment. Data analysis was performed using univariate and bivariate (independent t-test). The results showed the mean weight gain of LBW with incubator treatment and KMC was 20.7 grams/day and the mean weight gain of LBW with incubator treatment alone was 7.6 grams/day. The results of the analysis showed that there were differences in the weight gain of LBW who received incubator and KMC treatment and those who received incubator treatment only. Babies treated with the KMC have a relatively normal body temperature, a regular heart rate and breathing so that their body metabolism is better. KMC can be applied to any low birth weight baby, both while in the hospital and when the baby is at home. Keywords: Low Birth Weight Babies, Incubator, Kangaroo Method Care